2018
DOI: 10.1007/s00240-018-1055-9
|View full text |Cite
|
Sign up to set email alerts
|

Mini vs standard percutaneous nephrolithotomy for renal stones: a comparative study

Abstract: To compare the outcome of mini-percutaneous nephrolithotomy (Mini-PNL) versus standard-PNL for renal stones. Retrospective study was performed between March 2010 and May 2013 for patients treated by Mini-PNL or standard-PNL through 18 and 30 Fr tracts, respectively, using pneumatic lithotripsy. Semirigid ureteroscope (8.5/11.5 Fr) was used for Mini-PNL and 24 Fr nephroscope for standard-PNL. Both groups were compared in stone free rate(SFR), complications and operative time using Student-t, Mann-Whitney, Chi s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
2
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 21 publications
9
57
2
4
Order By: Relevance
“…Even a complex stone burden can be safely and efficiently managed with Mini PCNL . 12,13 In our series the stone free rate was significantly associated with number of stones (p = 0.004) and weakly associated with size (p = 0.3) and hardness (p = 0.2). Stone free rate was significantly lower with multiple calyceal stones in case of Mini PCNL.…”
Section: Methodssupporting
confidence: 45%
See 2 more Smart Citations
“…Even a complex stone burden can be safely and efficiently managed with Mini PCNL . 12,13 In our series the stone free rate was significantly associated with number of stones (p = 0.004) and weakly associated with size (p = 0.3) and hardness (p = 0.2). Stone free rate was significantly lower with multiple calyceal stones in case of Mini PCNL.…”
Section: Methodssupporting
confidence: 45%
“…Mini PCNL had significant advantage over standard PCNL in terms of reduced bleeding (mean haemoglobin drop of 0.8 mg%) leading to higher chance of tubeless procedure (75-80%) and reduced hospital stay (2.43-4.5 days). [11][12][13][14] The operative time for Mini PCNL was found to be 45-69 minutes which was higher than standard PCNL but statistically insignificant (p >0.3). 11,12 Kukreja et al 15 demonstrated similar safety and efficacy in his prospective randomised study in management of adult nephrolithiasis of size 15 to 30 mm with no difference in operative time between standard and Mini PCNL.…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…The MP studies have showed comparable and equal SFR and reduced comorbidities compared to conventional PCNL (8,14,15). ElSheemy et al compared MP and standard PCNL through 18 and 30 Fr tracts respectively (16). According to their results there was significant difference on SFR in between patients who had larger stone burden (>2cm 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally the miniaturization of PCNL has defined by diameter less than 20 Fr(7). The Minipercutaneous (MP) (16)(17)(18), Ultraminiperc (UMP) (11)(12)(13)(14) and Micropercutaneous (MicroPNL) (<10Fr) are currently feasible and modern alternatives with minimal invasiveness (2). The MP is accepted as suitable for renal stones <2 cm in size while UMP is for renal stones <1.5cm (7,8).…”
Section: Introductionmentioning
confidence: 99%